2019
DOI: 10.1371/journal.pone.0213505
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment neutrophil-to-lymphocyte ratio predicts clinical relapse of ulcerative colitis after tacrolimus induction

Abstract: Objectives Although tacrolimus is useful as an induction therapy in patients with ulcerative colitis (UC), information regarding the long-term outcome after tacrolimus therapy is insufficient. The aim of this study was to evaluate the clinical significance of the pretreatment neutrophil-to-lymphocyte ratio (NLR) as a prognostic factor in patients with UC receiving tacrolimus, to aid treatment selection. Materials and methods Patients with moderate-to-severe active UC wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
1
18
2
Order By: Relevance
“…While some studies have shown that high NLR predicts increased severity of active UC and CD, 61,62 low NLR has also been found to be strongly associated with risk of UC relapse in patients receiving tacrolimus therapy. 63 In our study, NLR evaluated at the threshold of 3 did not yield statistically significant associations with ICI colitis. In addition, our initial finding of decreased risk of ICI colitis in patients with NLR ≥ 5 was not confirmed in the confirmatory cohort.…”
Section: Discussioncontrasting
confidence: 55%
“…While some studies have shown that high NLR predicts increased severity of active UC and CD, 61,62 low NLR has also been found to be strongly associated with risk of UC relapse in patients receiving tacrolimus therapy. 63 In our study, NLR evaluated at the threshold of 3 did not yield statistically significant associations with ICI colitis. In addition, our initial finding of decreased risk of ICI colitis in patients with NLR ≥ 5 was not confirmed in the confirmatory cohort.…”
Section: Discussioncontrasting
confidence: 55%
“…On the other hand, GCs indicated the different behavior on lymphocyte numbers rather than neutrophil because GC results in the skew of T cells, activation of NF-κB via stimulation of Toll-like receptors [85], and activation of death-inducing genes and consequently induce apoptosis [86]. Observed increase and decrease in neutrophils and lymphocyte respectively resulted in a rise of NLR in hens administrated by GC Fluticasone that was similar to the some studies showing that treatments using GC had higher NLR values that are mainly derived by higher neutrophil counts [87]. Despite being none signi cant as compared to control, the BAA group had the lowest neutrophil percentage and NLR among other treatments and except to GC, BAA had the same effect on lymphocyte percentage with the other treatments.…”
Section: The Function Of Cellular and Humoral Immunitiessupporting
confidence: 78%
“…Elevated NLR which implies higher inflammatory burden signifies high neutrophil count due to active inflammation and low lymphocyte count correlating with defective response to the inflammatory process 22‐25 . In previous studies, high neutrophil counts have been associated with adverse prognosis in AD and AIS, whereas high lymphocyte counts have been associated with protective effects in cerebrovascular patients 6,14,26 .…”
Section: Discussionmentioning
confidence: 98%